(untitled) - Gicquel, Renaud (Boca Raton, 2013)
This book seeks to provide a basis for reflection on all global energy problems, offering an analysis of the main aspects to consider: energy supply, resource-dependent industries and technology available, macroeconomic implications of energy demand, geopolitical issues, and specifics of the situation in developing countries
Keywords: Power resources,Emergy policy,Chính sách năng lượng